(3GdMRH GdCYXe hGdhQO GdCaNes - (3GdgQhj, GdbGQj, CHh GdMSf, fhQ GdOjf (B- (3GdeqdG, Ydj Hf (B((3SdWGf(B) (3eMeO, (B1014 (3g`s ((3CMeO Hf CHj HcQ Hf YeQ Hf SbGas)
(3ChdgG (B:s
(3GdMeO ddg GdPj OYGfG ddEjeGfCeG HYO ajbhd Ydj Hf SdWGf eMeO GdbGQj deG QCjJ HYV GdSGdcjf jJYdbhf HChQGO GdeTGjN hgPG GdLeY gh eYOf GdOYGAhSejJgG GdMRH GdCYXe hGdhQO GdCaNes
(3BNQgG (B:s
(3Gddge Ud Ydi eMeO YHOc hQShdc GdfHj GdCej GdPj Bef Hc hHcJGHc hGYWg CaVd QMeJc hBJg GdTQa Ydi Ndbc jhe GdbjGeI hGLRg NjQ GdLRGA hGdSdGe Ydjg hQMeI Gddg hHQcGJg SHMGf QHc QH GdYRI YeG jUahfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 12s
(3eYLe GdeDdajf(B: 2 / 446s
(3cTa GdXfhf(B: 1 / 660s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs